Intellectual Capital and Firm Value: An Investigation of Turkish Manufacturing Companies - Çam, İlhan; Özer, Gökhan (Istanbul Univ, Sch Business, 2022)
This paper investigates whether intellectual capital and its components (human, relational, innovation, and process capitals) have meaningful information on firm value. Full sample consists of 148 listed Turkish manufacturing firms over the period of 2005-2017. We show that our extended Ohlson models explain the substantial part of the unexplained variation in firm market values. Specifically, we find that higher levels of measures of human capital, relational capital, process capital, innovation capital, and overall intellectual capital are directly associated with higher stock prices. Furthermore, we find that intellectual capital and its components have lagged effects on market values of firms, and human capital has a moderating effect on the relationship between other intellectual capital components and firm market values. Our main finding still holds when we re-estimate our model by addressing potential endogeneity issues and alternative conditions. Based on our findings, we recommend firm managers to do convenient resources planning on these components to raise the firm's value. Moreover, we recommend accounting standards setters to create a separate financial reporting standard, which includes detailed information on these components that are value-relevant in making business valuation decisions.
Keywords: Intellectual Capital; Human Capital; Relational Capital; Innovation Capital; Process Capital; Firm Value